A Cloud-based Sales and Stock Control System for Superstores under Non-zero Constant Lead Time Constraint - Fidelis Ikechukwu Onah; Jacinta Chioma Onuoha (JISR on Computing)
In today’s competitive business environment, effective sales and stock control system is a veritable tool for cutting down excessive revenue leakages in manufacturing and distribution companies as well as retail stores. And as investors strive to achieve profitability and growth through smart solutions, the use of cloud-based tools has now become more crucial for businesses than ever before. In this research study, advanced cloud-based sales and stock control software is written to improve accuracy in stock records, facilitate effective demand forecasting, reduce holding costs, minimize stock outs, ensure prompt customer order fulfillment, reduce order lead times, aid the decision-making process and subsequently maximize throughput. The methodology adopted in this study is the structured system analysis and design methodology (SSADM) which uses objects throughout the software development process. The programming languages and development tools used are HTML, CSS, JavaScript, PHP, SQL and JQUERY. The expected result is a user-friendly, easy to use and effective integrated sales and stock control system that will automate inventory tracking, demand forecasting, order processing and stock replenishment. The system will, therefore, offer huge cost savings, real-time visibility, automated workflows and seamless integration. The research findings indicate that the system will help streamline inventory operations, build customer loyalty, enhance accuracy and improve overall supply chain efficiency.